CLUSTERS OF MINERAL DEPOSITS OF THE SOUTHERN EAST SIBERIA AND PROSPECTS FOR THEIR DEVELOPMENT: AN OVERVIEW OF THE PROBLEM - Zh. V. Seminsky (Геодинамика и тектонофизика)
This study aims to identify the groups of closely spaced mineral deposits located in the Southern East Siberia and to describe these clusters. The mineral resource base of this region includes the deposits of lead, zinc, tungsten, tin, molybdenum, uranium, copper, gold, lithium, tantalum, niobium, silver, fluorite, zirconium, rare-earth metals, iron, mica, precious and semi-precious stones, oil, gas, and coal. Many of these deposits contain a significant part of the explored mineral reserves of Russia. The deposits are located in the tectonic structures of the Siberian platform (Tunguska syncline, Nepa arch, Cheremkhovo and Priangarie depressions), as well as in the fold belts framing the platform from the south and southeast (Baikal-Patom, Dzhida-Vitim, etc.). These structures and belts formed under the influence of plate tectonic and plume tectonic processes. This article describes the clusters of mineral deposits of the Angara, Sayan, Baikal and Transbaikalia regions. Currently, the most developed are the clusters located in the southern part of the study area (Shilka, Argun, Yeravnino, etc.). In the northern part (Mama-Bodaibo, etc.), the clusters have been either partially developed within the existing mining areas or are at the initial stage of development. In these territories, the road infrastructure, power supply and other facilities required for mining industry are either underdeveloped or lacking. Prospects for the regional development are related to the economic development of the territories adjacent to the Baikal-Amur railroad (BAM) and hydrocarbons production in the zone near the East Siberia – Far East oil pipeline. On the Siberian platform, mineral deposits formed during the stages of formation of its basement (Aldan, Anabar, and Sharyzhalgai shields) and platform cover (Tunguska syncline, and Nepa-Botuoba anticline). Within the fold frame, ore formation was associated with subduction, spreading, collision, and plume tectonic intraplate settings. To start the development of small-size deposits and mining of technogenic raw materials, it is advisable to establish exploration and production enterprises that can operate and manage expeditions and use compact ore-dressing plants.